One-Way Rotating Photonic Crystal Ring Resonator With High Quality Factor - Qiuyue Zhang; Xun Li (IEEE Photonics Journal)
We propose a planar photonic crystal ring resonator consists of a looped single interface between a regular and a magneto-optical photonic crystal structure. The cavity modes are shown to possess the unidirectional rotation characteristics, and the rotating direction is determined by the direction of an externally applied magnetic field normal to the rotation plane. This unique unidirectional feature results in the realization of cavity with extremely high Q factor of 3.2 × 106, more than one order of magnitude higher than the previous report for cavity with the same ring size [Z. Qiang, W. Zhou, and R. A. Soref, “Optical add-drop filters based on photonic crystal ring resonators,” Opt. Express, vol. 15, no. 4, pp. 1823–1831, Feb. 2007]. As an example of its applications, we present a unidirectional channel-drop filter design based on the one-way rotating photonic crystal ring resonator. Our simulation result shows that a 96.7% backward dropping efficiency can be achieved by this filter.